Passenger Transport Demand in Urban Areas : Methodology for Analysing and Forecasting (Paris : European Conference of Ministers of Transport, [Washington, D.C.: sold by OECD Publications Center, 1976)
All methods for analyzing or forecasting passenger transport demand in urban areas ultimately involve a model, i.e. a simplified representation of reality to help understand and predict the formation of demand. The present study therefore relates to urban transport demand modeling.
At head of title: Economic Research Centre.
Includes bibliographical references.
ne 27/02/2018
Loan
Keywords: Transportation; Urban Transportation